De Madrid a Turín: el ceremonial de las reinas españolas en la corte ducal de Catalina Micaela de Saboya - Río Barredo, María José del (Cuadernos de Historia Moderna, 2003)
This article studies the ceremonial of the Spanish Habsburg queens in the wake of its transfer to the court of Turin by Catalina Micaela, daughter of Philip II and wife of the Duke of Savoy from 1585 to 1597. Its purpose is to examine this ceremonial transfer in light of the widespread interest shown in the queen’s etiquette following its first systematic formulation in 1575, and to evaluate its potential for extending the political hegemony of the Spanish Monarchy.